Milesian Wool: A Risqué Metaphor in Aristophanes, Lysistrata 728-734. - Méndez Dosuna, Julián V. (Mnemosyne, 2021)
The author argues that the Milesian wool in the play "Lysistrata 729" by Aristophanes is a metaphor for female public hair. She discusses the dialogue between Lysistrata and the First Woman, previous interpretations of the passage, and an elucidation of the First Woman's true motives and intentions, and other fleece metaphors in Aristophanic comedy.